2021
DOI: 10.1103/physrevd.103.114015
|View full text |Cite
|
Sign up to set email alerts
|

Extending nuclear PDF analyses into the high- x , low- Q2 region

Abstract: We use the nCTEQ analysis framework to investigate nuclear Parton Distribution Functions (nPDFs) in the region of large x and intermediate-to-low Q, with special attention to recent JLab Deep Inelastic Scattering data on nuclear targets. This data lies in a region which is often excluded by W and Q cuts in global nPDF analyses. As we relax these cuts, we enter a new kinematic region, which requires new phenomenology. In particular, we study the impact of i) target mass corrections, ii) higher twist corrections… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…[15] where the effects were studied in more detail -see also Ref. [16]. Only those DIS data points with the hadronic invariant mass W ≥ 1.8 GeV are included in the analysis.…”
Section: Lepton-nucleus Dismentioning
confidence: 99%
See 1 more Smart Citation
“…[15] where the effects were studied in more detail -see also Ref. [16]. Only those DIS data points with the hadronic invariant mass W ≥ 1.8 GeV are included in the analysis.…”
Section: Lepton-nucleus Dismentioning
confidence: 99%
“…Fig.17The CMS 8 16. TeV Z-boson data[98,99] for nuclear modification R pPb compared with the EPPS21 fit.…”
mentioning
confidence: 99%
“…A pioneering work [12] showed that in order to accommodate these data within current fits, it is necessary to take into account target mass corrections [13]. Following these results the high-x data and, in particular, very precise recent data measured by the CLAS Collaboration [14] are now being included in the fits of the EPPS [9] and nCTEQ [15] groups. The latter study also considers nonperturbative multi-quark interactions and a special modelling of the nuclear effects in deuterium, which they have found to be crucial for the quality of the fit.…”
Section: Improvements In the Determination Of Npdfsmentioning
confidence: 99%
“…One of them, in collaboration with the CJ group, touches upon the use of available data from NC DIS in the high-x region, in particular the high precision JLAB 6 GeV data, and the impact on the valence quark distributions (D=452). By relaxing the cuts on virtuality and invariant mass more data enters in this nCTEQ15-HIX fit [21], in a kinematical region where higher twists effects become relevant. In particular those considered are targetmass corrections and non-perturbative multi-quark interactions.…”
Section: Nuclear Pdfsmentioning
confidence: 99%